Displacement hazard from distributed ruptures of strike-slip faults in the Tibetan plateau - Hu, Fangbo; Ren, Junjie (Frontiers in Earth Science, 2024)
Large strike-slip earthquakes are generally characterized by long surface rupture zones and relatively concentrated displacement distribution. The displacements on main seismogenic faults have been well studied and assessed by numerous empirical relations. Detailed mapping of the deformation zone of strike-slip earthquakes in the past decades indicates that distributed ruptures beyond the main faults have controlled the width of surface deformation zones and influenced the distribution of damages and earthquake-induced geological disasters. Therefore, the displacement hazard assessment from distributed surface rupture along strike-slip faults is urgent for disaster prevention and mitigation and the seismic safety of linear engineering. The Tibetan Plateau is marked by a series of strike-slip faults accompanied by lateral extrusion of material due to the Cenozoic collision of the Indian and Eurasian plates. In this study, we collected the surface rupture data of five strike-slip earthquakes in the Tibetan Plateau during the past decades, including the 1997 Mani (MW 7.5), 2010 Yushu (MW 6.9), 2014 Yutian (MW 6.9), 2021 Maduo (MW 7.4), and 2022 Menyuan (MW 6.6) earthquakes. Then, we preprocess the original data to form the standardized dataset after removing the fractures due to non-tectonic factors such as landslides, gravity instability under seismic ground motion, and so on. Based on the standardized dataset, the surface rupture displacements generated by strike-slip faults are incorporated into a probabilistic displacement hazard analysis framework, and a probability model of the surface rupture displacement distribution is established for the Tibetan Plateau. This model estimates the probability per unit area of finding a distributed rupture that allows a displacement that exceeds a displacement threshold at a given distance from the principal fault. This study not only provides a framework for the probabilistic displacement hazard of distributed ruptures from strike-slip faults but also supports the seismic hazard assessment of linear engineering crossing strike-slip faults in the Tibetan Plateau.